Progress and Diversity – New Paradigm of Development - Mateljan, Stjepan; Stančić, Hrvoje (2007)
Cultural diversity is important feature of humankind. Globalisation is latest incarnation of imperialism. Technological progress tends to replicate exact copies, instead to manufacture original functional solutions. In order to keep power, information society standardises world at it’s own image. Homogenization of world shifts balance between humankind and nature. Mankind is at unique spot in it’s history, not only as a cultural, but also as a biological being. Extinction of wildlife and extinction of languages are two faces of the same process. Technological progress focuses on narrow aspect of the world, while polluting all the others. We can separate technological progress from development. Technological progress is nomadic, and it’s property is constant expansion on new ‘feeding grounds’. Sustainable development is more evolutive, and focused on expansion in different niches of the same environment. Technology tends to make world standardized and easy to control, while neglecting it’s chaotic behaviour tendencies. From time of industrialization onwards the human impact on the Earth grew, and now is considerable factor of disbalance. Intellect is a limited problem solver. Digital divide is a great problem. While everyone is allegedly invited, to actively participate in the life of information society one must have infrastructure within reach, and some resources to either bid or use while participating. Equal standards in different contexts bring social stratification. Paradoxicaly, the greater the homogenization, the greater the social differences.
Projekt MZOS
ENG